Atividades Ligadas ao Programa Nacional de Erradicação da Febre Aftosa. - Sales, Nayara Fonseca (Universidade Federal do Tocantins, 2023)
The supervised curricular internship was conducted at the Agricultural Defense Agency of Tocantins (ADAPEC), at the Local Veterinary Unit of the municipality of Araguaína. The stage occurred from August 13 to November 20, 2018, totaling 402 hours under the supervision of Veterinarian Alessandro José Ferreira dos Santos. During the internship, several programs were followed, such as the National Program for the Control and Eradication of Brucellosis and Tuberculosis (PNCEBT), the National Program for Poultry Health (PNSA), the National Suicide Sanitation Program (PNSS) and the National Program for Eradication of Foot- ), active surveillance, surveillance and receipt of vaccines, and dairy supervision. For the effective participation in the preparation and execution of the second phase of the campaign for the vaccination of foot-and-mouth disease 2018, the present study discussed the main activities followed during the internship, with emphasis on the actions carried out during the vaccination campaign against this disease. It was verified the importance of the actions of the Defense Agency in PNEFA, so that it could evolve and maintain Tocantins as a FMD free state with vaccination, also demonstrating the preparation of the veterinarians involved for the next phase with the withdrawal of the vaccine and search to make Brazil a country free of this disease without vaccination.